THE FACTORS EFFECTING STUDENTS LACK ABILITY IN WRITING NARRATIVE TEXT FOR EIGHT GRADERS OF SMP NEGERI 05 KOTABUMI ACADEMIC YEAR 2021/2022 - Elis Susanti; Intan Aprilia; Rulik Setiani; Ollen Selvia Reni; Rokhma Dwi Widiastuti; Rifky Alvarez Satria Nugraha; Novi Yana Putri (Universitas Muhammadiyah Kotabumi, 2023)
In this study, the researcher discusses the factors effecting students' lack ability in writing narrative texts for eight graders of SMP Negeri 05 Kotabumi academic year 2021/2022. The researcher used descriptive qualitative research methods and the instruments used were data documents and interviews. The data collection technique used by the researcher was an in-depth interview technique with 18 students of class VIIIA. The results of this study illustrate there are 2 factors that effecting the students' lack of ability in writing narrative texts. Internal factors consist of health, interests, talents and motivation. The results of the research on students' internal health factors had no problems, there were 16 students who were not interested, there were 15 students who felt were not talent, and 12 students felt they did not motivation. External factors consist of family, surrounding environment and school. The results of external factors the students' families there were no problems, there were 15 students who did not receive support from the surrounding environment, and there was 1 student who had problems at school. Of the two factors, the most dominant factor influencing the students' lack of ability in writing narrative texts is the internal factor of interest.